Cancer mortality distribution in South Africa, 1997–2016 - Nhleko, Mandlakayise Lucky; Edoka, Ijeoma; Musenge, Eustasius (Frontiers in Epidemiology, 2023)
Introduction: The mortality data in South Africa (SA) have not been widely used to estimate the patterns of deaths attributed to cancer over a spectrum of relevant subgroups. There is no research in SA providing patterns and atlases of cancer deaths in age and sex groups per district per year. This study presents age-sex-specific geographical patterns of cancer mortality at the district level in SA and their temporal evolutions from 1997 to 2016. Methods: Individual mortality level data provided by Statistics South Africa were grouped by three age groups (0–14, 15–64, and 65+), sex (male and female), and aggregated at each of the 52 districts. The proportionate mortality ratios (PMRs) for cancer were calculated per 100 residents. The atlases showing the distribution of cancer mortality were plotted using ArcGIS. Spatial analyses were conducted through Moran’s I test. Results: There was an increase in PMRs for cancer in the age groups 15-64 and 65+ years from 2006 to 2016. Ranges were 2.83 (95% CI 2.77-2.89)-4.16 (95% CI 4.08-4.24) among men aged 15-64 years and 2.99 (95% CI 2.93-3.06)-5.19 (95% CI 5.09-5.28) among women in this age group. The PMRs in men and women aged 65+ years were 2.47 (95% CI 2.42-2.53)-4.06 (95% CI 3.98-4.14), and 2.33 (95% CI 2.27-2.38)-4.19 (95% CI 4.11-4.28). There were considerable geographical variations and similarities in the patterns of cancer mortality. For the age group 15-64 years, the ranges were 1.18 (95% CI 0.78-1.71)-8.71 (95% CI 7.18-10.47), p < 0.0001 in men and 1.35 (95% CI 0.92-1.92)-10.83 (95% CI 8.84-13.14), p < 0.0001 in women in 2016. There were higher PMRs among women in the Western Cape, Northern Cape, North West, and Gauteng compared to other areas. Similar patterns were also observed among men in these provinces, except in North West and Gauteng. Conclusion: The identification of geographical and temporal distributions of cancer mortality provided evidence of periods and districts with similar and divergent patterns. This will contribute to understanding the past, present, future trends and formulating interventions at a local level.